Population dynamics of selected ichthyofaunal components in the temperate, temporarily open/closed Kasouga Estuary, South Africa - Tweddle, Gavin Paul (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
The spatial and temporal pattern of ichthyofaunal community composition in relation to selected physico-chemical (temperature and salinity) and biological variables (chlorophyll-a and zooplankton) was investigated at ten stations in the temperate temporarily open/closed Kasouga estuary. In addition, the food web structure in the estuary was investigated using stable carbon isotope analysis. Results of the 5 metre seine net survey indicated that ichthyofaunal composition and biomass in the Kasouga estuary was largely determined by seasonality and mouth condition. Maximum abundance and biomass of ichthyofauna was recorded during summer or during those periods when overtopping occurred. Overtopping coincided with the recruitment of marine estuarine dependant species, which dominated the catches both numerically and in biomass. The recruitment of these species resulted in an increase in diversity of the ichthyofaunal community. There were no significant spatial patterns in the distribution of smaller ichthyofauna (<50mm SL) identified in Bray-Curtis similarity matrices using cluster analysis (Primer 5 v5.2.4). Spearman's correlation analysis revealed that there were no significant correlations between abundance and biomass of ichthyofauna and selected physico-chemical and biological variables other than salinity (P>0.05 in all other cases). There were two distinct spatial patterns in the distribution of the larger ichthyofauna (>50mm SL). These corresponded to a grouping associated with the mouth region and a grouping associated with the remaining regions of the estuary. Stable isotope analysis indicated that the primary source of carbon utilised by the ichthyofauna of the Kasouga estuary was derived from the channel, most likely microphytobenthic algae. The contributions of the riparian and salt marsh vegetation to the total carbon flow appear to be minimal.
Keywords: Estuaries -- South Africa -- Eastern Cape; Estuarine fishes -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape